Dead or alive? Antipredatory mechanism of Adenomera hylaedactyla (Cope, 1868) (Anura: Leptodactylidae) in northeastern Brazil (Somma: Revista Científica do Instituto Federal do Piauí, 2024)
Anurans inhabit different types of environments, so these animals have developed a wide variety of defense mechanisms throughout evolutionary processes. During fieldwork in Serra dos Matões, municipality of Pedro II, state of Piauí, northeastern Brazil, we found an individual of Adenomera hylaedactyla on the edge of a permanent watercourse, in a transition area between Cerrado and Caatinga. Upon contact, the specimen exhibited “limb interweave” behavior, in which the individual extends and intertwines the hind limbs as a defense mechanism. There are no records of this defense mechanism in Adenomera species, making this work the first documented record of “limb interweave” for this genus. It should be emphasized that the evolution of species is closely related to the different types of behavior exhibited during interspecific interactions, therefore, such behaviors can influence speciation processes.